Body atlas the human design - Burst, Barbara; Discovery Health Channel ([S.l.] : Discovery Health Channel, 2003)
Exploration of human body. Hi-tech photography shows blood flowing through veins ; food digesting in the intestines and oxygen being processed by the lungs.
Executive producer, Mary Ellen Iwata
Narrator: Alex Chadwick
Keywords: Body human -- Composition; Physiology; Human anatomy